2021
DOI: 10.1093/jn/nxab088
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding Practices in 80 Low- and Middle-Income Countries: Prevalence of and Socioeconomic Inequalities in Dietary Diversity, Meal Frequency, and Dietary Adequacy

Abstract: Background Adequate complementary feeding practices in early childhood contribute to better food preferences and health outcomes throughout the life course. Objectives The aim of this study was to describe patterns and socioeconomic inequalities in complementary feeding practices among children aged 6–23 mo in 80 low- and middle-income countries. Methods We a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
54
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 21 publications
16
54
1
2
Order By: Relevance
“…Our result of pro-rich wealth-related inequalities in MDD was in line with previous studies [ 28 , 32 ]. Although no study has assessed education-related inequality in MDD, the distribution of infant and young child feeding indicators was higher among mothers with higher education in several studies [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our result of pro-rich wealth-related inequalities in MDD was in line with previous studies [ 28 , 32 ]. Although no study has assessed education-related inequality in MDD, the distribution of infant and young child feeding indicators was higher among mothers with higher education in several studies [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 93%
“…Dietary diversity increases with economic improvements [ 12 , 28 ]; however, Indonesia may not be the case. Over the last 22 years, Indonesia experienced a substantial economic change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition is an essential component of the Sustainable Development Goal (SDG) 2 which focuses on zero hunger by 2030 [1]. However, many parents, particularly those in low-and middle-income countries struggle to provide dietary diversity for children [2]. Dietary diversity is considered to be an outcome of the nutritional status of children [3,4] and a key component of high-quality diets [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Marginalisation is linked to poverty [53][54][55]; the Indigenous Batwa communities are among the poorest communities in the world [18]. Studies have shown how wealth index and education level influences nutritional status [56,57]; indeed, both Batwa and Bakiga populations have extremely low education levels and income, and suffer from undernutrition and stunting, especially in children under 5 years [20].…”
Section: Discussionmentioning
confidence: 99%